Leadership Style, Work Engagement and Organizational Commitment Among Nurses in Saudi Arabian Hospitals - AL-Dossary RN (Dove Medical Press, 2022)
Reem N AL-Dossary Nursing Education Department, College of Nursing, Imam Abdulrahman Bin Faisal University, Dammam, 34221, Saudi ArabiaCorrespondence: Reem N AL-Dossary, Nursing Education Department, College of Nursing, Imam Abdulrahman Bin Faisal University, Dammam, 34221, Saudi Arabia, Email rnaldosari@iau.edu.saPurpose: The purpose of this paper is to examine how nurse managers' leadership styles, work engagement, and nurses' organizational commitment are related in Saudi Arabia.Methods: This study used a cross-sectional design using an online survey instrument targeted at nurse managers and nurses working in Saudi Arabian hospitals. Multi-factor leadership questionnaire (MLQ), organizational commitment questionnaire (OCQ), and Utrecht Work Engagement Scale (UWES) were used in the Questionnaire. The survey link is forwarded to HR administrators of 71 hospitals, which includes public, private, and public-private partnership hospitals. The survey link was active from 27th November 2021 to 18th December 2021, and at the end of the survey, 394 responses were received. After removing the incomplete responses, 390 participant responses are considered for data analysis. t-tests and correlation analysis are used to analyze the data.Results: Among the participants, 84.4% of the participants were nurses and 15.6% were nurse managers. Significant difference (p < 0.05) of opinions is observed among nurse managers in relation to transformational and transactional leadership styles and engagement. Transformational and transactional leaderships are positively correlated with organizational commitment and nurses' engagement.Conclusion: Differences in leadership style perceptions among nurses and nurse managers reflected issues in nursing management, which have to be addressed in light of rapid infrastructural changes owing to Saudi vision 2030.Keywords: leadership, nurses' engagement, organizational commitment